Pemenuhan Hak Atas Kesehatan terhadap Anak Stunting di Jawa Timur dalam Perspektif Hak Asasi Manusia - Miftah, Farrah (Universitas Batanghari Jambi, 2024)
This research uses a qualitative and normative approach to determine the implementation of children's rights to health in the context of stunting in East Java. This study examines the normative aspects of human rights (HAM) in the context of stunting through policy analysis, in-depth interviews, and document review. The results show that policy implementation does not fully reflect human rights principles and access to health services is uneven in some areas. This study recommends the need for policy reform that is more consistent with human rights principles, as well as increased implementation of interventions to increase the realization of children's right to health. By combining qualitative and normative approaches, this research contributes to a deeper understanding of the challenges and opportunities in realizing children's right to health in the context of stunting in East Java.